Cigarette Smoking Is Negatively Associated with the Prevalence of Type 2 Diabetes in Middle-Aged Men with Normal Weight but Positively Associated with Stroke in Men - Su Wang; Jie Chen; Yuzhong Wang; Yu Yang; Danyu Zhang; Chao Liu; Kun Wang (Journal of Diabetes Research)
Background. The prevalence of diabetes and potentially related complications, including stroke, is rapidly increasing in China. The long-term effects of lifestyle may affect glucose metabolism in the general population. Although some studies have shown an association between smoking and the risk of type 2 diabetes mellitus (T2DM), the relationship remains unclear. Furthermore, the relationship between smoking and stroke in patients with T2DM has not been fully elucidated. Objective. We investigated the influence of cigarette smoking on T2DM and stroke in China. Detailed questionnaires about smoking status and anthropometric measurement were completed by participants, and oral glucose tolerance testing (OGTT), hemoglobin A1c (HbA1c), homeostasis model assessment of IR (HOMA-IR), and blood lipids were measured. Results. In total, 8196 adults aged 40 years or older were included. We found a reduced risk of impaired glucose regulation (IGR) and T2DM in male smokers with normal weight (body mass index BMI<25 kg/m2 or waist circumference WC<90 cm) compared with nonsmokers after adjusting for age, alcohol intake, physical activity, educational level, family history of diabetes, SBP, DBP, TG, TC, HDL-C, and LDL-C. However, no significant association was detected in male current smokers with overweight/obesity or female smokers. In addition, compared with nonsmokers without T2DM, current smokers with T2DM had a significantly higher risk of stroke (odds ratio: 2.64, 95% confidence interval: 1.25–5.57; P=0.011) after adjusting for confounders. Conclusions. Smoking was negatively associated with T2DM in Chinese men of normal body weight, but no significant association was found for men with overweight/obesity or women. In addition, smoking was positively associated with nonfatal stroke, especially in patients with T2DM. Further prospective studies are needed to examine the association between smoking, diabetes, and stroke in different ethnic groups.